Solar electricity basics : powering your home or office with solar energy - Chiras, Daniel D. (New Society Publishers, 2020)
"Solar Electricity Basics is a highly readable introduction to a promising technology, ideal for homeowners, business owners, builders, and students. It covers everything you need to work with solar electricity including sizing a solar electric system, types of systems, how systems operate, and costs and benefits."--